2019
DOI: 10.1111/ggi.13732
|View full text |Cite
|
Sign up to set email alerts
|

Daily sleep duration and the risk of incident disability among younger elderly Japanese adults in the New Integrated Suburban Seniority Investigation Project: A prospective study using competing event analysis

Abstract: Aim: This study aimed to investigate the association between daily sleep duration and incident disability among younger elderly individuals in Japan. Methods:We carried out a prospective cohort study, the New Integrated Suburban Seniority Investigation Project, including 1895 (962 men and 933 women) Japanese physically and socially independent individuals aged ≥65 years. Information on daily sleep duration, demographic, lifestyle characteristics and medical status were collected by questionnaire and health che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Lu et al showed that individuals with long sleep duration had a higher incidence of dementia [ 40 ]. Zhang et al revealed that shorter sleep duration (<6 h/day) was associated with a higher risk of functional disability when considering death as a competing event [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al showed that individuals with long sleep duration had a higher incidence of dementia [ 40 ]. Zhang et al revealed that shorter sleep duration (<6 h/day) was associated with a higher risk of functional disability when considering death as a competing event [ 41 ].…”
Section: Resultsmentioning
confidence: 99%